The Effectiveness of Corporate Management Training on MSME Owners of Dharma Bhakti Astra Foundation Partner - Rizky Surya; M. Syamsul Maarif; Sadikin Kuswanto (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
MSMEs have an important role and strategic in national economic development. The presence of MSMEs can increase workforce absorption, encourage economic growth and distribution of development results. In managing SMEs, skills and knowledge are required by the owner to be able to run the business properly, which can be acquired through the corporate management training program. This research aims to analyze the effectiveness of a corporate management training program by seeing the competencies and performances of business owners after participating in training and creating an effective strategy to increase performance through the corporate management training program. The sample collection method in this study is census sampling from 30 respondents who participated in a management training program. Collected data is analyzed using Structural Equation Modeling – Partial Least Square (SEM-PLS) Smart PLS 2.0 program for all variables and also Analytical Hierarchy Process (AHP). The result of the findings shows that training influenced competency and performance significantly, while competency also influenced performance significantly. The alternative strategy that becomes a priority is to adjust the training topic specifically according to business owner needs. This study will be useful for institutions or training organizers for MSMEs in the future. Keywords: management training, competencies and performances, MSMEs, SEM-PLS, AHP